Peran Good Corporate Governance Memediasi Pengaruh Profitabilitas terhadap Nilai Perusahaan di BEI Periode 2019-2023 - Simanullang, Febri Yanti; Gultom, Robinhot; Purba, Jon Hendri (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to obtain empirical evidence of Good Corporate Governance in mediating profitability on firm value. The sample used in this study were all Industrials sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period using the purposive sampling method. The software analysis used was WarpPLS version 8.0. The results of this study indicate that the capital structure and profitability variables directly have a negative effect on firm value and the dividend policy variable directly shows a positive effect on firm value. The test results prove that Good Corporate Governance is able to mediate the effect of profitability on firm value.